Comparison of Analgesic Efficacy of Ultrasound-Guided Erector Spinae Plane Block with Local Anesthetic Infiltration Wound Site in Patients Undergoing Posterolateral Thoracotomy - Waseem, Syed Majid; Haider, Zulfiqar; ., Abdullah; Saeed, Muhammad; Khalique, Abdul; Amjad, Muhammad Ammar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effects of preoperative ultrasound-guided Erector spinae plane block with local anesthetic wound site infiltration on postoperative pain score and opioid consumption in patients undergoing posterolateral thoracotomy. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anesthesia and Pain Management Combined Military Hospital, Multan Pakistan from Dec 2022 to May 2023. Methodology: Sixty adult patients undergoing posterolateral thoracotomy were allocated randomly in two Groups, Erector spinae plane block Group X (n=30) and wound infiltration Group Y (n=30). In the ultrasound-guided Erector spinae plane block Group, Erector spinae plane block was performed with 0.5% Bupivacaine 20 ml at the level of thoracic vertebrae 5. In contrast, in the Wound Infiltration Group, 20 ml of 0.5% Bupivacaine was injected along the line of the surgical incision and also at the site of chest tube placement postoperatively. The postoperative opioid consumption and mean pain score at 01 hours, 06 hours, 12 hours, and at 24 hourS were assessed. Results: Compared with the wound site infiltration Group, the mean Pain scores at 1 hour, 06 hours, 12 hours, and 24 hours were significantly less in the ESPB Group (p<0.001). Moreover, postoperative opioid consumption in the Erector spinae plane block Group was also significantly reduced postoperatively. Conclusion: Compared to wound infiltration with local anesthetics, Ultrasound-guided erector spinae block could significantly reduce the postoperative pain score opioid consumption and reduce the incidence of opioids induced complications in patients undergoing thoracotomy.